A retrospective study of traditional Chinese medicine as an adjunctive therapy for patients with chronic heart failure. Issue 30 (July 2018) - Sui, Yan-bo; Liu, Li; Tian, Qi-yuan; Deng, Xiao-wei; Zhang, Yi-qing; Li, Ze-guang
Abstract : Abstract: This study retrospectively evaluated the effectiveness and safety of traditional Chinese medicine Shenqilixin Formula (SQLXF) as an adjunctive intervention for treating patients with chronic heart failure (CHF). This retrospective study included 135 patients with CHF. They were allocated to a treatment group or a control group according to the different treatments they received. Seventy five patients in the treatment group underwent SQLXF plus routine treatment, while 60 subjects in the control group received routine treatment only. The primary outcome was cardiac function. It was measured by the left ventricular end diastolic diameter (LVDD), left ventricular ejection fraction (LVEF), cardiac output (CO), every cardiac output (ECO), and cardiac index (CI). The secondary outcome included motor function. It was measured by the standard 6-MinuteWalk Test (6MWT). In addition, adverse events (AEs) were also recorded. Compared to subjects in the control group, patients in the treatment group revealed greater effectiveness in cardiac function, measured by LVEF ( P < .05), CO ( P < .05), and ECO ( P < .05), and motor function, measured by the 6MWT scale ( P < .05). Moreover, no significant differences of AEs were found between the 2 groups. SQLXF as an adjunctive therapy to routine treatment may help to improve both cardiac and motor function in patients with CHF.